Shift work disorder among nurses during the COVID-19 pandemic in Saudi Arabia - Jay Ablao; Mathar Mohideen Nagoor Thangam; Raghad Saif; Rawan Alamri; Wasan Almashhori; Reham Alshehri; Sarah Alemrani (Rev Rene)
Objective: to assess the prevalence of shift work disorder symptoms among nurses who work multiple shifts for long hours during COVID-19 pandemic. Methods: descriptive cross-sectional study was utilized in this study of 120 nurses working in governmental hospitals in Saudi Arabia. The study used structured questionnaires: Hospital Anxiety and Depression Scale, to measure anxiety and depression, Epworth Sleepiness Scale to measure sleepiness and insomnia, and Fatigue Severity Scale to measure fatigue. Results: this study showed high prevalence shift work disorder symptoms such as daytime sleepiness (59.2%), fatigue and anxiety (42.5%) across all departments during the COVID-19 pandemic. Also, it showed a 30.5% borderline depression. Significant difference between the educational attainment, hours of working and working departments with Anxiety was identified. Significant difference was found between educational attainment and hours of working with depression. Conclusion: the nurses suffered shift work disorder symptoms during the COVID-19 pandemic. Contributions to practice: shift work alters the nurses’ lifestyle and their health. Little research has conducted on shift work disorder among the nurses on the prevalence and its effects. The results are useful to identify the issues and to overcome the difficulties, which will help to keep the essentials of quality of care.